2020
DOI: 10.32756/0869-5490-2020-2-21-29
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 1007 intensive care unitpatients with SARS-CoV-2 pneumonia

Abstract: Федеральный дистанционный консультативный центр анестезиологии и реаниматологии на базе Первого МГМУ им. И.М. Сеченова

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 34 publications
1
6
0
12
Order By: Relevance
“…Another study from the USA showed that the proportion of DM among patients hospitalized due to COVID-19 constituted 31.8 %, which was substantially higher than that among non-hospitalized patients with mild disease course (5.4 %) [ 24 ]. A study conducted in Russian Federation on a large cohort of patients presenting with acute respiratory distress syndrome secondary to COVID-19 revealed the underlying DM in 25 % of cases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study from the USA showed that the proportion of DM among patients hospitalized due to COVID-19 constituted 31.8 %, which was substantially higher than that among non-hospitalized patients with mild disease course (5.4 %) [ 24 ]. A study conducted in Russian Federation on a large cohort of patients presenting with acute respiratory distress syndrome secondary to COVID-19 revealed the underlying DM in 25 % of cases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Сеченова, куда были включены 1007 больных COVID-19. Авторы показали, что острый респираторный дистресс-синдром, вызванный SARS-CoV-2, чаще развивается у лиц старше 40 лет при наличии сердечно-сосудистых заболеваний, сахарного диабета 2-го типа и/или ожирения [15].…”
Section: Discussionunclassified
“…Сходные данные получены и в нашем ретроспективном исследовании на основании анализа более 1 тыс. пациентов с SARS-CoV-2-пневмонией, которым потребовались респираторная поддержка и госпитализация в отделение реанимации и интенсивной терапии (ОРИТ) лечебных учреждений Российской Федерации [8]. Более 90% этих пациентов в возрасте старше 40 лет, а у 70% имелись различные сопутствующие заболевания, в том числе артериальная гипертония (АГ), ишемическая болезнь сердца (ИБС), фибрилляция предсердий (ФП), инсульт в анамнезе и др.…”
Section: сведения об авторахunclassified